2014
DOI: 10.1007/s00586-014-3674-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to curve progression in female patients with adolescent idiopathic scoliosis treated with a brace

Abstract: This study suggests that Risser sign, the magnitude of the major curve at pre-brace, apical vertebral rotation, and the spinal length increasing velocity are important factors to predict progression in the girls with AIS. Risser sign cannot predict the progression of scoliosis accurately unless combined with other related parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…It is used to determine if an adolescent is under-weight (<5th percentile of sex and age-specific BMI), normal weight (5th to 85th percentile) or over-weight (>84th percentile). O’Neill et al (2005)79 found that over-weight AIS patients had 3.1 times more possibilities to fail in brace treatment than those not over-weighted. Progression over 45 ο happened in 45% of over-weight and 28% of normal.…”
Section: Resultsmentioning
confidence: 99%
“…It is used to determine if an adolescent is under-weight (<5th percentile of sex and age-specific BMI), normal weight (5th to 85th percentile) or over-weight (>84th percentile). O’Neill et al (2005)79 found that over-weight AIS patients had 3.1 times more possibilities to fail in brace treatment than those not over-weighted. Progression over 45 ο happened in 45% of over-weight and 28% of normal.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [22] retrospectively studied the curve behavior of 89 braced AIS female patients. In his work, logistic regression analysis demonstrated that Risser score of less than 2 is one of the prognostic factors for curve progression by more than 5˚.…”
Section: Low Level Of Skeletal Maturitymentioning
confidence: 99%
“…Four articles identified rotation (apical rotation, rib hump and rib vertebral angle are all considered as rotation related) as a risk factor for curve progression [22,25−27]. In a sample of 89 patients, Zhang et al [22] described above noted that apical vertebral rotation beyond grade 3 is one of the risk factors for curve progression of more than 5˚. In another retrospective study [27], a comparison of patients having corrective surgery to patients defined with a nonprogressive curve was made in an attempt to identify three-dimensional parameters by an EOS system in a sample of 133 patients.…”
Section: Vertebral Rotationmentioning
confidence: 99%
“…In this study we investigated the predictive value of BMD, in addition to other well-known risk factors, on curve progression to the surgical threshold (Cobb angle ≥ 45°). Previous prognostic studies mostly defined curve progression as Cobb angle increment ≥6° 916. Nevertheless, such increment of Cobb angle may not exert direct clinical significance, e.g., the treatment plan may not be affected even curve progress from 20° to 26°.…”
Section: Discussionmentioning
confidence: 99%